OPPORTUNITIES OF THE ONLINE LEARNING FROM STUDENTS’ PERSPECTIVES: CASE STUDY IIUM STUDENTS - Mohd Khairul Azmi Hassan; Siti Sarah Mohd Zubir; Norshita Mat Nayan (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The Covid-19 pandemic spread rapidly and had negative consequences on the most of the sectors in Malaysia. As a result of the enforcement of Movement Control Order (MCO) and the need to maintain a certain physical distance in order to combat the pandemic, universities and schools have temporarily closed. Online learning has completely replaced in-person learning in order to keep the educational process running as usual. This paper aims to discover the opportunities of online learning system from the perspective of students in International Islamic University of Malaysia (IIUM) during pandemic via online survey. Based on previous literatures, a few factors that significantly contributed to the opportunities of online learning gained by the students, which are: 1) Course Content, 2) Course Assessment, 3) Social Interaction, 4) Instructor Characteristics, 5) Technological Skills and 6) Time Management. In this article, a research model and hypotheses also were developed prior to data analysis. The collected data were then analysed using SPSS to gain the results. The descriptive statistics, correlation analysis using Pearson Correlation Coefficients, and multiple regression analysis was conducted. The result of correlation and multiple regression analysis revealed a significant relationship between the independent variables and dependent variable. Besides, two hypotheses were supported with the dependent variable which are Course Content and Course Assessment. The study also found that the best factor that has the highest influence on the opportunities of online learning in IIUM, which is Course Content. The results of the study contribute to the body of knowledge about the prospects of online learning by looking at the factors and their findings, which may be an important step to understand and improve the online learning system in the future.